2009
DOI: 10.1007/s11232-009-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Toward a quantum generalization of equilibrium statistical thermodynamics: ħ-k Dynamics

Abstract: We show that the quantum statistical mechanics (QSM ) describing the quantum and thermal properties of objects only has the sense of a particular semiclassical approximation. We propose a more general microdescription than in QSM of objects in a thermal bath with the vacuum explicitly taken into account; we call it -k dynamics. We construct a qualitatively new model of the object environment, namely, a quantum thermal bath. We study its properties including the cases of a "cold" and a "thermal" vacuum. We intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In ref. 1, we showed that, in the general case, these vacuum states are described by the family of complex wave functions that are dependent on the particular choice of parameters and .…”
Section: Thermal Equilibrium States and Family Of States Generated Atmentioning
confidence: 91%
See 3 more Smart Citations
“…In ref. 1, we showed that, in the general case, these vacuum states are described by the family of complex wave functions that are dependent on the particular choice of parameters and .…”
Section: Thermal Equilibrium States and Family Of States Generated Atmentioning
confidence: 91%
“…We now discuss the invariance of the zeroth law with respect to the transitions between equilibrium thermal CCSs at nonzero temperatures. To do this, we use the invariance of the zeroth law with respect to the Lorentz group O (2,1). This can be demonstrated in the simplest way using the comment to formula (27).…”
Section: Invariance Of the Zeroth Law Of Stochastic Thermodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Umezawa recognized that he failed to solve this prob lem in the context of the thermal field dynamics developed by him. We will show in this article and sub sequent one that our approach (called (ប, k) dynam ics [2][3][4][5][6]) apparently allows us to come as close to this target as possible.…”
Section: The Problem Of Incorporating Thermodynamics Into Quantum Theorymentioning
confidence: 99%